Policy Advocacy in Resolving an Environmental Preservation Conflict: A Case of Policy Advocacy between the Government, Private Sector and Society in Kayen, Pati, Central Java - Ramaditya Rahardian Daneswara; Ibnu Fath Zarkasi (Magister Administrasi Publik, 2019)
The quality of first category karst has attracted investors to build a cement factory in the Kendeng Mountains. This interest investor later received various responses by the local community who joined the community rejecting the cement factory, Jaringan Masyarakat Peduli Pegunungan Kendeng (JMPPK). The rejection was based on the reasons that the establishment of a cement factory in the area would have an impact on the local environment in general and pollution, degradation and damage to springs, loss of agricultural land and employment opportunities accompanying farmers, the spread of certain diseases that would endanger the communities living in around it. Specifically, this article examines the use of advocacy strategies involving formal and informal initiatives undertaken by the Kendeng community to influence the local government's decision to issue operational licenses to build a cement factory in Kayen District, Pati District based on environmental considerations. This article uses a qualitative research design. The results showed that the policy advocacy initiative, which included formal and informal channels by the Gunung Kendeng Community Care Network to influence policy in issuing operational licenses for the construction of the Kayen cement plant, proved successful. Policy advocacy culminated in a decision of the highest court that ruled against an operational permit that the local government had given to a local subsidiary of PT Indocement to build a cement factory in the Kayen area.